Make It Simple: (SR-A1+TLR7) Macrophage Targeted NANOarchaeosomes - Parra, Federico Leonel; Caimi, Ayelen Tatiana; Altube, Maria Julia; Cargnelutti, Diego Esteban; Vermeulen, Mónica Elba; de Farias, Marcelo Alexandre; Portugal, Rodrigo Villares; Morilla, Maria Jose; Romero, Eder Lilia (Frontiers in Bioengineering and Biotechnology, 2018)
Hyperhalophilic archaebacteria exclusively produce sn2,3 diphytanylglycerol diether archaeolipids, unique structures absent in bacteria and eukaryotes. Nanovesicles made of archaeolipids known as nanoarchaeosomes (nanoARC), possess highly stable bilayers, some of them displaying specific targeting ability. Here we hypothesize that nanoARC made from Halorubrum tebenquichense archaebacteria, may constitute efficient carriers for the TLR7 agonist imiquimod (IMQ). NanoARC-IMQ takes advantage of the intense interaction between IMQ and the highly disordered, poorly fluid branched archaeolipid bilayers, rich in archaeol analogue of methyl ester of phosphatidylglycerophosphate (PGP-Me), a natural ligand of scavenger receptor A1 (SR-A1). This approach lacks complex manufacture steps required for bilayers labelling, enabling future analytical characterization, batch reproducibility and adaptation to higher scale production. SR-A1 mediated internalization of particulate material is mostly targeted to macrophages and is extensive because it is not submitted to a negative feedback. A massive and selective intracellular delivery of IMQ may concentrate its effect specifically into the endosomes, where the TLR7 is expressed, magnifying its immunogenicity, at the same time reducing its systemic bioavailability, and therefore it’s in vivo adverse effects. NanoARC-IMQ (600-900 nm diameter oligolamellar vesicles of ~ -43 mV Z potential) were heavily loaded with IMQ at ~44 µg IMQ/mg phospholipids (~20 folds higher than the non-SR-A1 ligand soyPC liposomes loaded with IMQ (LIPO-IMQ)). In vitro, nanoARC-IMQ induced higher TNF-α and IL-6 secretion by J774A1 macrophages compared to same dose of IMQ and same lipid dose of LIPO-IMQ. In vivo, 3 subcutaneous doses of nanoARC-IMQ+ 10 g total leishmania antigens (TLA) at 50 g IMQ per Balb/C mice, induced more pronounced DTH response, accompanied by a nearly 2 orders higher antigen-specific systemic IgG titers than IMQ+TLA and LIPO-IMQ. The isotype ratio of nanoARC-IMQ+TLA remained ~0.5 indicating, the same as IMQ+TLA, a Th2 biased response distinguished by a pronounced increase in antibody titers, without negative effects on splenocytes lymphoproliferation, with a potential CD8+LT induction 10 days after the last dose. Overall, this first approach showed that highly SR-A1 mediated internalization of heavily loaded nanoARC-IMQ, magnified the effect of IMQ on TLR7 expressing macrophages, leading to a more intense in vivo immune response